Microbiota-Immune System Interactions in Human Neurological Disorders - Huang, Qin; Yu, Fang; Liao, Di; Xia, Jian (CNS & Neurological Disorders - Drug Targets, 2020)
Recent studies implicate microbiota-brain communication as an essential factor for physiology and pathophysiology in brain function and neurodevelopment. One of the pivotal mechanisms about gut to brain communication is through the regulation and interaction of gut microbiota on the host immune system. In this review, we will discuss the role of microbiota-immune systeminteractions in human neurological disorders. The characteristic features in the development of neurological diseases include gut dysbiosis, the disturbed intestinal/Blood-Brain Barrier (BBB) permeability, the activated inflammatory response, and the changed microbial metabolites. Neurological disorders contribute to gut dysbiosis and some relevant metabolites in a top-down way. In turn, the activated immune system induced by the change of gut microbiota may deteriorate the development of neurological diseases through the disturbed gut/BBB barrier in a down-top way. Understanding the characterization and identification of microbiome-immune- brain signaling pathways will help us to yield novel therapeutic strategies by targeting the gut microbiome in neurological disease.
Keywords: microbiota-immune system